Pengembangan Sistem Informasi Sewa Mobil dan Paket Wisata berbasis Web menggunakan Teknologi Framework Laravel (Studi Kasus: "Mobil Kampus") - Ronaldo Grasberg Wijaya; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Today's business development utilizes technology to manage information and provide efficient and effective services for consumers. This facilitates all business processes, as well as minimizing business risks. This research takes a case study of the Mobil Kampus company, which is a service company that offers tour package services in Malang, Batu and surrounding areas. Mobil Kampus was founded in 2011 and became one of the recommended car rental companies in Malang. However, there are often obstacles for consumers, such as the mismatch of information about the cars available on the spot, as well as miscalculations of transactions that become obstacles for company owners. Therefore, an information system was created to help companies to list the available cars, types of tour packages, culinary information and cost information. The web-based information system uses the development method Software Development Life Cycle (SDLC)with the model waterfall. In the system design stage, modeling is done in the form of UML diagrams based on functional requirements, then implemented through program code using the PHP programming language and the framework Laravel. Then tested with themethod black box testing and testing usability. Black box testing obtained 100% valid results andtesting usability obtained a score of 72.5 which was included in the good category, with a grade scale C and acceptance value is acceptable.